Survival Rates of Patients Treated by Home and Hospital Dialysis and Cadaveric Renal Transplantation - Moorhead, John F. (1970)
Of 109 patients admitted to the renal failure programme of the Royal Free Hospital 80·7% were surviving after six years. For patients on home dialysis the four-year rate was 86·2%, more deaths occurring in women than in men. The short-term survival rate of all patients was high—namely, 96·3% at six months and 94·4% at 12 months. Hence large increases in the rate of acceptance of patients as well as successful transplantation are necessary to balance acceptance and loss from this programme.